2012
DOI: 10.5152/jtgga.2012.02
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of tumoral angiogenesis with HIF-1 alpha and microvessel density in women with endometrium cancer

Abstract: Objective: Hypoxia inducible factor 1 alpha (HIF-1α) is a nuclear protein upregulated in response to reduced cellular oxygen concentration which therefore acts as a marker for hypoxia. The aim of this study was to determine tumoral angiogenesis with immunohistochemical markers in endometrium cancer and its relation with stage, grade, survival rates and other prognostic factors. Material and Methods:Using the database in our Gynecologic Oncology clinic, we selected 94 patients who were diagnosed with endometria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A possible explanation is that tumor hypoxia induces the overexpression of HIF-1α, which is associated with a higher MVD. 31,32 We also found that the tumor with rich stroma had a higher HIF-1α expression. The previous study by us 13 showed that the tumor with rich stroma had a higher D value.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…A possible explanation is that tumor hypoxia induces the overexpression of HIF-1α, which is associated with a higher MVD. 31,32 We also found that the tumor with rich stroma had a higher HIF-1α expression. The previous study by us 13 showed that the tumor with rich stroma had a higher D value.…”
Section: Discussionmentioning
confidence: 51%
“…In addition, this study showed that the high HIF‐1α expression group had higher MVD than the low‐expression group. A possible explanation is that tumor hypoxia induces the overexpression of HIF‐1α, which is associated with a higher MVD . We also found that the tumor with rich stroma had a higher HIF‐1α expression.…”
Section: Discussionmentioning
confidence: 73%
“…These findings were consistent with previous reports in tumors. MVD was higher in nuclear HIF-1A expression, and nuclear HIF-1A determined the functional activity of the HIF-1A complex 35 , 36 . In normal gallbladder tissues, we found that MVD in cytoplasm HIF-1A + /nuclear HIF-1A - subgroup was significantly higher than that of cytoplasm HIF-1A - /nuclear HIF-1A + subgroup.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, perfusion parameters obtained from the TIC analysis during CEUS examination were significantly associated with micro-vessel density (MVD) of endometrial cancer [22]. It was suggested that the MVD is an indirect marker of the intensity of tumor vascularization, which is known to be associated with the progression of endometrial cancer and survival outcome [24,25]. Therefore, perfusion parameters obtained from the TIC analysis during CEUS examination may be associated with prognosis of endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%